SCRS Conference Proceedings on Intelligent Systems 2021
DOI: 10.52458/978-93-91842-08-6-46
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble based Effective Intrusion Detection System for Cloud Environment over UNSW-NB15 Dataset

Abstract: Advanced computing innovations are rapidly evolving, resulting in the advent of new organizational and operational strategies. Cloud computing has emerged as one of the pre-eminent innovation in the recent years. Cloud computing enables its clients to access flexible, distributed computing domain via internet. Cloud has manifested itself as a viable framework that facilitates the use of application domains, data and infrastructural facilities that mainly encompasses workstations, network and storage infrastruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In [29], the authors suggested an intrusion detection system based on machine learning models to detect attacks in IoT networks. They evaluated their model based on data captured by IoT sensors using Node MCU ESP8266, DHT 11 sensor, and wireless router.…”
Section: Ensemble Machine Learning Classificationmentioning
confidence: 99%
“…In [29], the authors suggested an intrusion detection system based on machine learning models to detect attacks in IoT networks. They evaluated their model based on data captured by IoT sensors using Node MCU ESP8266, DHT 11 sensor, and wireless router.…”
Section: Ensemble Machine Learning Classificationmentioning
confidence: 99%
“…The rules are processed with the occurrence of events; otherwise, they are classified as intrusion. 11 Due to the exponential advancement of technology and the increasing number of hacking tools, the capacity for adaptation is regarded as a critical attribute. In order to effectively address a greater number of network intrusions, it is necessary to implement either a semi-automatic or automated detection phase.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge base contains predefined rules for rule‐based anomaly identification. The rules are processed with the occurrence of events; otherwise, they are classified as intrusion 11 . Due to the exponential advancement of technology and the increasing number of hacking tools, the capacity for adaptation is regarded as a critical attribute.…”
Section: Introductionmentioning
confidence: 99%